1995
DOI: 10.1037/0735-7036.109.3.222
|View full text |Cite
|
Sign up to set email alerts
|

Song sharing reflects the social organization in a captive group of European starlings (Sturnus vulgaris).

Abstract: The social organization of captive groups of adult male and female starlings caught in different localities was studied to understand the possible social basis of song sharing. In the nonbreeding season, the social organization was based on within-sex groups or pairs and a few intersexual pairs. The pattern of song sharing clearly reflected the social organization. Members of the social pairs of females shared most of their songs, whereas males shared songs with other males to an extent that depended on their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
144
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(155 citation statements)
references
References 53 publications
9
144
2
Order By: Relevance
“…This is done to maximize the effects of social learning in acquiring the response, given that previous studies have indicated that social learning is enhanced if the model and observer are in close physical proximity ( Aisner and Terkel, 1992; Coussi-Korbel and Fragaszy, 1995; Hausberger et al, 1995). It is important to note that we did not see evidence that rats were inadvertently pressing the active lever by trying to interact with their partner, because there was no preference for the active versus inactive lever in the early days of testing prior to the acquisition of drug selfadministration, nor was there a preference for one lever or the other in cocaine naïve rats that never received cocaine.…”
Section: Discussionmentioning
confidence: 99%
“…This is done to maximize the effects of social learning in acquiring the response, given that previous studies have indicated that social learning is enhanced if the model and observer are in close physical proximity ( Aisner and Terkel, 1992; Coussi-Korbel and Fragaszy, 1995; Hausberger et al, 1995). It is important to note that we did not see evidence that rats were inadvertently pressing the active lever by trying to interact with their partner, because there was no preference for the active versus inactive lever in the early days of testing prior to the acquisition of drug selfadministration, nor was there a preference for one lever or the other in cocaine naïve rats that never received cocaine.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of duetting by a mated pair has been hypothesized to help cement and maintain the pair bond in some bird species, and thus is potentially a sexually selected trait (Langmore, 1998;Todt & Hultsch, 1982;Wickler, 1980). Beyond these demonstrations of particular current utility of birdsong there are a number of more speculative hypotheses that are plausible (e.g., song as a group ''password'' (Feekes, 1982), for social cementing (Hausberger, Richard-Yris, Henry, Lepage, & Schmidt, 1995), or for family bonding (Ritchison, 1983)). Furthermore, ''song'' per se is not necessarily a valid unitary category in some species, which have multiple song types involved in mating vs. territoriality (Morse, 1970), and there can be overlap in the function of songs and calls (Marler & Slabbekoorn, 2004).…”
Section: The Adaptive Functions Of Birdsongmentioning
confidence: 99%
“…In European starlings, individuals sometimes share songs with other group members, and it has been observed that patterns of song sharing reflect the social organization. During the nonbreeding season, females tend to associate in same-sex social pairs, and pair members share most of their songs (Hausberger, Richard-Yris, Henry, Lepage, & Schmidt, 1995). Subsequent playback experiments have demonstrated that females are able to distinguish past song types.…”
Section: Vocal Plasticity and Vocal Learningmentioning
confidence: 99%